CD69+ resident memory T cells are associated with graft‐versus‐host disease in intestinal transplantation. Issue 5 (17th February 2021) - Weiner, Joshua; Svetlicky, Nina; Kang, Jiman; Sadat, Mohammed; Khan, Khalid; Duttargi, Anju; Stovroff, Merrill; Moturi, Sangeetha; Kara Balla, Abdalla; Hyang Kwon, Dong; Kallakury, Bhaskar; Hawksworth, Jason; et al.
Abstract : Graft‐versus‐host disease (GvHD) is a common, morbid complication after intestinal transplantation (ITx) with poorly understood pathophysiology. Resident memory T cells (TRM ) are a recently described CD69+ memory T cell subset localizing to peripheral tissue. We observed that T effector memory cells (TEM ) in the blood increase during GvHD and hypothesized that they derive from donor graft CD69+TRM migrating into host blood and tissue. To probe this hypothesis, graft and blood lymphocytes from 10 ITx patients with overt GvHD and 34 without were longitudinally analyzed using flow cytometry. As hypothesized, CD4+ and CD8+CD69+TRM were significantly increased in blood and grafts of GvHD patients, alongside higher cytokine and activation marker expression. The majority of CD69+TRM were donor derived as determined by multiplex immunostaining. Notably, CD8/PD‐1 was significantly elevated in blood prior to transplantation in patients who later had GvHD, and percentages of HLA‐DR, CD57, PD‐1, and naïve T cells differed significantly between GvHD patients who died vs. those who survived. Overall, we demonstrate that (1) there were significant increases in TEM at the time of GvHD, possibly of donor derivation; (2) donor TRM in the graft are a possible source; and (3) potential biomarkers for the development and prognosis of GvHD exist. Abstract : In the largest study to date of graft‐versus‐host disease after intestinal transplantation, donor resident memory cells in the graft appear to play a key pathophysiological role, informing potential biomarkers for disease development and prognosis.